ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOAN PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. PERIODE 2008-2015 - Intan Lestari (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aim is to know about internal factors and external factors which are influences for the Non-Performing Loan on Bank Negara Indonesia in period 2008-2015.This research was conducted with quota sampling. The data used in this study were obtained from the Banking Quarterly Report 2008-2015 and Bank Indonesia Quarterly Report. Methods of data analysis using multiple linear regression analysis to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Bank Size, Economic Growth, and Inflation to Non - Performing Loan (NPL) of Bank Negara Indonesia.Based on the test for normality, autocorrelation test, multicolinearity test and heteroscedasticity test, there were no deviations from goodness of fit. The result of the research simultanly shows that CAR, LDR, bank size, economic growth and inflation influence significantly against NPL. The result of the research partially shows that variables like CAR, bank size, economic growth and inflation infulence significant against NPL, while LDR influence not significant against NPL. The coefficient determinant (R2) of 93.3% shows that NPL can be explained by the variables of the research.Keywords: NPL, CAR, LDR, bank size, economic growth, inflation